Regulation of Leishmania populations within the host. I. the variable course of Leishmania donovani infections in mice. - Bradley, D J (1977)
The course of infection with Leishmania donovani was followed in seven strains of laboratory mice with measurement of the liver parasite burdens over 20 weeks. The acute parasite population growth rate varied greatly between, but not within, strains. Four strains were relatively resistant with less than an eight-fold increase while the three acutely susceptible strains showed over an eight-fold increase in the first month. Thereafter, one initially susceptible strain showed a dramatic fall in parasite numbers with histological liver damage while another strain maintained an immense parasite load for up to 2 years involving mononuclear phagocytes throughout the body. The system provides a model for studying genetic control of resistance to intracellular infection and the range of responses is compared with human leprosy and cutaneous leishmaniasis.